Determinants of COVID-19 vaccine acceptance and access among people experiencing homelessness in Germany: A qualitative interview study - Grune, Julianna; Savelsberg, Darius; Kobus, Marta; Lindner, Andreas K.; Herrmann, Wolfram J.; Schuster, Angela (Frontiers in Public Health, 2023)
Introduction People experiencing homelessness face lower life expectancy, higher prevalence of somatic and mental diseases and a more difficult access to healthcare compared to people in secure living. During the COVID-19 pandemic transmission rates were higher among people experiencing homelessness and preventive public health measures were not properly adapted to the specific needs of people experiencing homelessness. Thus, goal of our study was understanding the determinants of acceptability and access of the COVID-19 vaccine. Materials and methods We conducted a qualitative interview study with twenty guideline interviews with adult people currently experiencing homelessness in Berlin, Germany (August 2021 – April 2022). Participants were approached in a purposive sampling strategy. The interviews were analyzed with qualitative content analysis according to Mayring. Results Acceptance and attitude toward the COVID-19 vaccine is influenced by confidence in the vaccine as well as in the political and healthcare system, the individual COVID-19 risk perception and sense of collective responsibility. Overall, the acceptance of the vaccine was high among our participants. Facilities offering low threshold COVID-19 vaccines for people experiencing homelessness were perceived as helpful. Language barriers and the need for identity documents were major barriers to access the COVID 19 vaccine. Discussion People experiencing homelessness are a marginalized and vulnerable group often underrepresented in the public and scientific discourse. During the COVID-19 pandemic, preventive public health measures, including the COVID-19 vaccine, failed to consider specific needs of people experiencing homelessness. Multidimensional strategy to enhance inclusive healthcare are needed to improve access and to reduce discrimination and stigmatization.